2019
DOI: 10.15587/1729-4061.2019.159310
|View full text |Cite
|
Sign up to set email alerts
|

Development of a device for the optimal reception of signals against the background of an additive three-component interference

Abstract: particularly unacceptable where a communication system is integrated into the overall system of a technological process safety system. The described situation occurs specifically during railroad transportation in the technological communication systems and subsystems that transfer signals from railroad automatics. As the saturation of industries, transport, and even households, with such integrated systems grows, solving the tasks on noise-resistant receival of information signals becomes increasingly relevant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…It is shown that the statistically justified estimates of the parameters of the pseudo-signal are the estimates obtained by minimizing the isolated logarithms of the likelihood ratio of the signal and each of the structurally deterministic interference (ILLRN). These ILLRNs were introduced in [5]; they are the summands of both modifications of the objective function. The terms of the objective function not included in the ILLRN are calculated on the basis of the above estimates and make corrections to the values of both modifications of the objective functions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is shown that the statistically justified estimates of the parameters of the pseudo-signal are the estimates obtained by minimizing the isolated logarithms of the likelihood ratio of the signal and each of the structurally deterministic interference (ILLRN). These ILLRNs were introduced in [5]; they are the summands of both modifications of the objective function. The terms of the objective function not included in the ILLRN are calculated on the basis of the above estimates and make corrections to the values of both modifications of the objective functions.…”
Section: Discussionmentioning
confidence: 99%
“…Its presence is not a consequence of solving a single problem of synthesizing an optimal receiver. The combination of such a synthesis and taking into account structurally deterministic interference was demonstrated in [5]. It presents the results of the synthesis of a device for optimal signal reception against the background of an additive three-component interference.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
See 2 more Smart Citations